2018
DOI: 10.1186/s12893-018-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative dynamics and significance of plasma-free amino acid profiles in colorectal cancer

Abstract: BackgroundFor early detection of cancer, we have previously developed the AminoIndex Cancer Screening (AICS) system, which quantifies 6 plasma-free amino acids (PFAAs) in blood samples. Herein, we examined the usefulness of the AICS in patients with colorectal cancer (CRC) by comparing the preoperative and postoperative PFAA profiles.MethodsOur study cohort consisted of 62 patients who had undergone curative resection for CRC at our cancer center, with no recurrence at the time of the study. Blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
4
6
0
Order By: Relevance
“…Furthermore, similar ndings were reported for other types of cancers [26,27]. Therefore, changes in amino acid pro les, e.g., AICS values, before and after treatment may be used to predict prognosis and monitor recurrence in patients with several cancers [4,10,26,27].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, similar ndings were reported for other types of cancers [26,27]. Therefore, changes in amino acid pro les, e.g., AICS values, before and after treatment may be used to predict prognosis and monitor recurrence in patients with several cancers [4,10,26,27].…”
Section: Discussionsupporting
confidence: 75%
“…We recently reported that AICS (lung) abnormalities in patients with lung cancer may be normalized (from rank C to A or B), when the tumor is completely removed, indicating that AICS (lung) values show some reversibility based on the disease condition [10]. Furthermore, similar ndings were reported for other types of cancers [26,27]. Therefore, changes in amino acid pro les, e.g., AICS values, before and after treatment may be used to predict prognosis and monitor recurrence in patients with several cancers [4,10,26,27].…”
Section: Discussionsupporting
confidence: 69%
“…We recently reported that most patients preoperatively diagnosed with rank C potentially exhibited a reduction in the AICS (lung) rank if they were cured after surgery [10]. Furthermore, similar ndings were reported for other types of cancers [27,28]. In contrast, some NSCLC patients without AICS (lung) abnormalities in the preoperative test, namely, those diagnosed with rank A or B, also showed tumor recurrence, even after curative resection.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, some NSCLC patients without AICS (lung) abnormalities in the preoperative test, namely, those diagnosed with rank A or B, also showed tumor recurrence, even after curative resection. These ndings demonstrated that the condition of AICS (lung) abnormalities themselves may not only re ect the tumor-bearing status in patients, but may also be strongly associated with some biological grade of malignant characteristics associated with tumor proliferation, invasiveness, and/or metastasis [4,10,27,28]. However, no signi cant differences were observed in recurrence patterns in the present cohort, suggesting that AICS (lung) abnormalities are not associated with the metastatic route.…”
Section: Discussionmentioning
confidence: 46%
“…Aminoindex Cancer Screening (AICS, Ajinomoto Co., Inc.) system is a blood test based on multivariate analysis of plasma-free amino-acids (PFAA) [370,371]. The AICS assay has been validated in a series of clinical trials covering approximately 2,500 patients with 7 different types of cancer and 15,000 healthy controls [372][373][374]. The AICS test is currently being used to screen for early detection of lung cancer in Japan [372,375].…”
Section: Translational Statusmentioning
confidence: 99%